A high-yield synthesis and acid–base response of phosphate-templated [3]rotaxanes. Issue 94 (4th November 2016) - Qiao, Bo; Liu, Yun; Lee, Semin; Pink, Maren; Flood, Amar H.
Abstract : We show a high-yielding synthesis (80%) of [3]rotaxanes using shape-persistent macrocycles, cyanostars, and anionic organo-phosphate templates catalyzed by low steric-demand click chemistry. Abstract : Anion-templated rotaxanes are a rare class of functional organic molecules capable of novel switching and mechanical behaviors. Yet, investigations of these properties are limited by existing synthetic strategies. We show a high-yielding synthesis (80%) of [3]rotaxanes using shape-persistent macrocycles, cyanostars, and anionic organo-phosphate templates catalyzed by low steric-demand click chemistry. The reaction yields correlate with the template's binding affinities. Use of longer linkers relieves steric congestion to enable a reversible acid–base response, opening the way to molecular switching.